Sulfur metabolism in beef cattle and management strategies to improve performance and health in newly weaned beef cattle - Neuhold, Kelley L., author; Wagner, John, advisor; Engle, Terry, advisor; Peel, R. Kraig, committee member; Rollin, Bernard, committee member (Colorado State University. Libraries, 2012)
To view the abstract, please see the full text of the document.
Keywords: hydrogen sulfide; sulfur; receiving; performance; Cattle